Structural, magnetic and dielectric properties of magnesium doped nickel ferrite nanoparticles - H., Moradmard; S., Farjami Shayesteh; P., Tohidi; Abbas, Zulkifly; M., Khaleghi (Elsevier, 2015)
Magnesia doped nickel ferrite nanopowders (Ni1−xMgxFe2O4, x = 0, 0.1, 0.3, 0.5, 0.7) have been synthesized by co-precipitation method and all samples were annealed at 900 °C. The structural, morphological and magnetic properties of the products were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), energy-dispersive X-ray (EDX) spectroscopy and vibrating sample magnetometer (VSM). Also microwave dielectric properties were measured at frequencies 1 GHz–12 GHz. XRD analysis indicates that all samples have spinel structure and there is not any extra phase in all samples. The increase in magnesia concentration caused to variation in the average crystallite size and lattice constant. Doping magnesia in nickel ferrite gave rise to a decrease in the saturation magnetization whereas doping led to increase in coercivity field. The parameters like dielectric constant, dielectric loss and ac conductivity of the nanoparticles samples are studied in the frequency range from 1 to 12 GHz. All these parameters show, size dependent variations. Complex dielectric permittivity of samples was decreased by increasing in frequency.